Virtue, rules, and justice Kantian aspirations - Hill, Thomas E. (Oxford : Oxford University Press, 2012)
The author interprets & extends Kant's moral theory in a series of essays that highlight its relevance to contemporary ethics. He introduces the major themes of Kantian ethics & explores its practical application to questions about revolution, prison reform, & forcible interventions in other countries for humanitarian purposes.
Description based on online resource; title from home page (viewed on July 12, 2012).
Includes bibliographical references and index.
Keywords: Kant, Immanuel, -- 1724-1804.; Ethics